2016
DOI: 10.1016/j.bbmt.2015.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Inolimomab and Etanercept for Severe Steroid-Refractory Acute Graft-versus-Host Disease

Abstract: Steroid-refractory acute graft-versus-host disease (aGVHD) remains an important cause of morbidity and mortality after allogeneic stem cell transplantation (SCT). A protocol on the management of aGVHD was introduced in our center that incorporated a prospective study on combination therapy with inolimomab (anti-IL-2Rα) and etanercept (anti-tumor necrosis factor-α) for steroid-refractory aGVHD. We evaluated the efficacy and safety in 21 consecutively treated patients. The patients had developed refractory aGVHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…As expected in the clinical setting of this study, infections were relatively common; however, the incidence of infection did not differ substantially from that in previous reports or in our institutional controls [21,39,40]. The multifaceted immune defects due to the presence-and treatment-of GVHD itself, the disruption in the mucosal barrier due to GI GVHD, and/or dysbiosis can explain the majority of these infections, particularly the C difficile infections and enterococcal bacteremia [41].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…As expected in the clinical setting of this study, infections were relatively common; however, the incidence of infection did not differ substantially from that in previous reports or in our institutional controls [21,39,40]. The multifaceted immune defects due to the presence-and treatment-of GVHD itself, the disruption in the mucosal barrier due to GI GVHD, and/or dysbiosis can explain the majority of these infections, particularly the C difficile infections and enterococcal bacteremia [41].…”
Section: Discussionsupporting
confidence: 68%
“…Two patients developed a Clostridium difficile infection, and 1 of them died due to pseudomembranous colitis. Moreover, although 5 patients developed bacteremia (with infection by enterococci in 2 patients, staphylococci in 2 patients, and Klebsiella oxytoca in 1 patient), the incidence rate (25%) was not higher than that reported in historical controls [21].…”
Section: Safetymentioning
confidence: 65%
See 2 more Smart Citations
“…They concluded that the combination of inolimomab and etanercept failed to improve the dismal prognosis of severe SR-aGVHD. 33 Two factors may be related to our superior outcomes of the combination treatment by basiliximab and etanercept. First, as TNF inhibitors, etanercept, and infliximab have different structures and modes of action.…”
Section: Discussionmentioning
confidence: 99%